Effects of Bicarbonate Stress on Serum Ions and Gill Transporters in Alkali and Freshwater Forms of Amur Ide (Leuciscus waleckii) - Chang, Yu Mei; Zhao, Xue Fei; Liew, Hon Jung; Sun, Bo; Wang, Shuang Yi; Luo, Liang; Zhang, Li Min; Liang, Li Qun (Frontiers in Physiology, 2021)
The Amur ide Leuciscus waleckii a member belongs to the Cyprinidae family which known highly tolerance to alkaline condition at > pH 9. However, the ionoregulatory mechanism in regulating alkaline adaptability remain unclear. Therefore, this study was planned to investigate the effect of bicarbonate on acid-base balancing and ionoregulation responses. Comparatively, ions and acid-base regulation were explored for the alkali form and ancestral freshwater form Amur ide under the 50 mmol/L bicarbonate exposure, assembly the alkalinity of Lake Dali Nor. The serum pH and ions (e.g., Na+, K+, Cl– and Ca2+), Na+/K+-ATPase (NKA) activity and mRNA expression of gill transporters (NKA, NHE2/3, NBC1, AE1, NCC, NKCC1, SLC26A5 and SLC26A6) in two forms of Amur ide acclimated to alkalinity were found significantly different. Specifically, serum Na+ with mRNA levels of NCC, NHE and NKA, of serum Cl- with NKCC1 and NBC1 were highly correlated, whereas bicarbonate transporters like SLC26A5 and SLC26A6 were found expressed in the alkali form of Amur ide. We proposed that the alkali form of Amur ide has evolved the strong ability to maintain ions and acid-base balance via basolateral NKA alongside with NKCC1 and NBC1, and apical ionic transporters, especially NCC to link with other transporters (SLC26) to achieve the transepithelial Cl- and Na+ uptake/base secretion function during alkalinity challenge. Thus, we suggested that the alkali form of Amur ide would acclimate more effectively to alkaline water than its freshwater form, which require long period of alkaline acclimation. This study provides new insights of the physiological mechanisms in alkali form of Amur ide adapt to alkaline condition.